Fibrous Hamartoma of Infancy in the Eyelid: A Rare Presentation. Issue 6 (November 2016) - Tran, Ann Q.; Thuro, Bradley A.; Albert, Daniel M.; Lucarelli, Mark J.; Potter, Heather D.
Abstract : A 6-year-old girl presented with a left nodular mass around the punctum. Previous debulking in a similar location at 10 weeks and 8 months of age confirmed fibrous hamartoma of infancy. Pathology at the initial surgery revealed benign-appearing fibroadipose tissue, vasculature, and smooth muscle. Pathologic examination from the third debulking illustrated less fibrous trabeculae extending into increased amounts of mature-appearing adipocytes with collections of immature-appearing fibrocytes. The lesion had slight differences in pathology compared with prior surgical specimens; however, was still consistent with fibrous hamartoma of infancy. No recurrence has been reported since the last surgery. Abstract : A case report of a 6-year-old girl who presented with a recurrent eyelid fibrous hamartoma of infancy six years after initial removal.